Tretan Muslim Dark Jokes: A Critical Study on Summon Podcast Content - Mawardi, Imam; Hidayatullah, Ahmad Fauzan; Octafiani, Tri Utami (the Faculty of Ushuluddin, UIN Sunan Gunung Djati Bandung, 2022)
The Somasi event on Deddy Corbuzier's Youtube channel is a stand-up comedy show on Youtube. The comedy material is called dark jokes. From the Dark Jokes that Tretan Muslims conveyed about religion in the show, this article attempts to analyse the value of tolerance internalised in comedy. This research focused on one video upload in a summon event entitled